Analisis Tingkat Keseimbangan (Balance) Mahasiswa Program Studi Pendidikan Kepelatihan Olahraga Semester VI - Jasri Jasri; Meliskawati Didipu; Mohamad Hendrik Hadia; Nangsi Manggopa; Dzul Fahri Ahmad Dumoi; Syardiansyah H Madanun; Zulkifli Balango (-, 2026)
This study aimed to determine and analyze the balance ability of sixth-semester students of the Sports Coaching Education Study Program. The research employed a quantitative approach using a descriptive method. The subjects consisted of 10 students selected through purposive sampling technique. Data collection was carried out using the Stork Stand Test to measure students’ static balance ability. The data were analyzed using descriptive percentage analysis to identify the improvement in students’ balance ability. The results showed that the average pre-test score of 19.4 seconds increased to 29.2 seconds in the post-test after balance training was conducted for eight meetings. The average improvement of 9.8 seconds indicated that balance training had a positive effect on students’ body stability ability. Regular balance exercises were able to improve movement coordination, postural control, and the ability to maintain the body’s center of gravity more steadily. Therefore, the balance training program was considered effective in improving the balance ability of students in the Sports Coaching Education Study Program.